2015
DOI: 10.1007/s11892-015-0659-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Memory T Cells in Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) is a chronic autoimmune disease that leads to progressive destruction of pancreatic beta cells. Compared to healthy controls, a characteristic feature of patients with T1D is the presence of self-reactive T cells with a memory phenotype. These autoreactive memory T cells in both the CD4(+) and CD8(+) compartments are likely to be long-lived, strongly responsive to antigenic stimulation with less dependence on costimulation for activation and clonal expansion, and comparatively resistant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 83 publications
1
32
0
Order By: Relevance
“…In a multicenter, randomized, double-blind, placebo-controlled clinical trial of recent onset T1D patients, treatment with alefacept, preserved their C-peptide secretion, reduced insulin use and hypoglycemic events, and induced favorable immunologic profiles at one year, even after one year of termination of therapy. As expected, alefacept treatment in this study, significantly depleted CD4 + and CD8 + central memory T cells (Tcm) and effector memory T cells (Tem), preserved Tregs, increased the ratios of Treg to Tem and Tcm, and increased the percentage of PD-1 expressing CD4 + Tem and Tcm [20,21]. Preservation of Tregs, was the major finding in the T1DAL trial, and was plausibly due to the lower expression of CD2 on Tregs compared to the higher levels on memory T cells.…”
Section: Successessupporting
confidence: 85%
See 1 more Smart Citation
“…In a multicenter, randomized, double-blind, placebo-controlled clinical trial of recent onset T1D patients, treatment with alefacept, preserved their C-peptide secretion, reduced insulin use and hypoglycemic events, and induced favorable immunologic profiles at one year, even after one year of termination of therapy. As expected, alefacept treatment in this study, significantly depleted CD4 + and CD8 + central memory T cells (Tcm) and effector memory T cells (Tem), preserved Tregs, increased the ratios of Treg to Tem and Tcm, and increased the percentage of PD-1 expressing CD4 + Tem and Tcm [20,21]. Preservation of Tregs, was the major finding in the T1DAL trial, and was plausibly due to the lower expression of CD2 on Tregs compared to the higher levels on memory T cells.…”
Section: Successessupporting
confidence: 85%
“…Alefacept has not only been used for the treatment of psoriasis but was successfully repurposed for other diseases that involved T cell activation such as type I diabetes (T1D) [20,21], preconditioning in allogeneic hematopoietic stem cell transplantation (HSCT) of pediatric patients with life-threatening nonmalignant diseases [22], kidney and liver transplantation [23][24][25], atopic dermatitis (AD) [26,27],…”
Section: Repurposing Of Alefacept In Different Human Diseases: Succesmentioning
confidence: 99%
“…Various studies have indicated that Tm cells confer resistance to traditional immunosuppression, are difficult to eliminate by depletion therapies and have limited dependence on co-stimulatory blockage strategies (32,33). Hence, the present study adopted a strategy of applying anti-CXCL10 antibodies alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, progress has been hampered by lack of direct access to the site of pathology, limitations of peripheral blood assays, and non-standardized immunologic assessments. Nevertheless, results from recent trials indicate that improved technologies and use of standardized mechanistic assessments can yield new insights into the pathology, progression, and treatment of T1D [7,57]. Fig.…”
Section: Trial Endpointsmentioning
confidence: 99%
“…Although autoreactive T cells can also be detected in the peripheral blood of healthy subjects, the hallmark of autoreactive T cells in T1D is their memory phenotype [57]. However, frequencies of autoreactive T cells in peripheral blood are low and available technologies are not sensitive enough to be practical in the clinical trial setting and blood volume constraints.…”
Section: Trial Endpointsmentioning
confidence: 99%